Advances in accounting behavioral research. Vol. 5 - Arnold, Vicky (Emerald, 2002)
The world of accounting is subject to the vagaries of human nature just like any other profession. These papers represent research into the behavioural aspects and leadership challenges facing those working in the profession in 21st century.
Keywords: Business & Economics -- Accounting -- General.; Personnel & human resources management.; Accounting.; Accounting -- Psychological aspects -- Research.; elektronické knihy; electronic books